Population Pharmacokinetic, Pharmacogenetic, and Pharmacodynamic Analysis of Cyclophosphamide in Ethiopian Breast Cancer Patients - Ahmed, Jemal Hussien; Makonnen, Eyasu; Bisaso, Ronald Kuteesa; Mukonzo, Jackson Kijumba; Fotoohi, Alan; Aseffa, Abraham; Howe, Rawleigh; Hassan, Moustapha; Aklillu, Eleni (Frontiers in Pharmacology, 2020)
Cyclophosphamide (CPA) containing chemotherapy regimen is the standard of care for breast cancer treatment in sub-Saharan Africa. Wide inter-individual variations in pharmacokinetics (PK) of Cyclophosphamide (CPA) influence the efficacy and toxicity of CPA containing chemotherapy. Data on the pharmacokinetics (PK) profile of CPA and its covariates among black African patients is lacking. We investigated population pharmacokinetic/pharmacogenetic/pharmacodynamic (PK-PG-PD) of CPA in Ethiopian breast cancer patients. During the first cycle of CPA-based chemotherapy, the population PK parameters for CPA were determined in 267 breast cancer patients. Absolute neutrophil count was recorded at baseline and day 20 post CPA administration. A population PK and covariate model analysis was performed using non-linear mixed effects modeling. Semi mechanistic and empiric drug response models were explored to describe the relationship between the area under concentration-time curve (AUC), and neutrophil toxicity. One compartment model better described CPA PK with population clearance and apparent volume of distribution (VD) of 5.41 L/hr and 46.5 L, respectively. Inter-patient variability in CPA clearance was 51%. Patients carrying CYP3A5*3 or *6 alleles had lower elimination rate constant and longer half-life compared to wild type carriers. CYP2C9 *2 or *3 carriers were associated with increased clearance of CPA. Patients who received 500 mg/m2 based CPA regimen were associated with a 32.3% lower than average clearance and 37.1% lower than average VD compared to patients who received 600 mg/m2. A 0.1 m2 unit increase in body surface area (BSA) was associated with a 5.6% increment in VD. The mean VD (33.5 L) in underweight group (BMI<18.5 kg/m2) was significantly lower compared to those of overweight (48.1 L) or obese patients (51.9 L) (p < 0.001). AUC of CPA was positively correlated with neutropenic toxicity. In conclusion, we report large between-patient variability in clearance of CPA. CYP3A5 and CYP2C9 genotypes, BSA, BMI and CPA dosage regimen influence PK of CPA. Plasma CPA exposure positively predicts chemotherapy-associated neutropenic toxicity.